Mind wandering and sleep in daily life: a combined actigraphy and experience sampling study - Marcusson-Clavertz, David; Persson, Stefan D.; Davidson, Per; Kim, Jinhyuk; Cardeña, Etzel; Kühner, Christine (Consciousness and cognition, 2023)
Individuals who sleep poorly report spending more time mind wandering during the day. However, past research has relied on self-report measures of sleep or measured mind wandering during laboratory tasks, which prevents generalization to everyday contexts. We used ambulatory assessments to examine the relations between several features of sleep (duration, fragmentation, and disturbances) and mind wandering (task-unrelated, stimulus-independent, and unguided thoughts). Participants wore a wristband device that collected actigraphy and experience-sampling data across 7 days and 8 nights. Contrary to our expectations, task-unrelated and stimulus-independent thoughts were not associated with sleep either within- or between-persons (n = 164). Instead, individual differences in unguided thoughts were associated with sleep disturbances and duration, suggesting that individuals who more often experience unguided train-of-thoughts have greater sleep disturbances and sleep longer. These results highlight the need to consider the context and features of mind wandering when relating it to sleep.
Online verfügbar: 2. Dezember 2022, Artikelversion: 2. Dezember 2022
Gesehen am 09.09.2024